Changes in per capita CO2 emissions of six large Japanese cities between 1980 and 2000: An analysis using "The Four System Boundaries" approach. (January 2020) - Murakami, Kae; Kaneko, Shinji; Dhakal, Shobhakar; Sharifi, Ayyoob
Highlights: We compare per capita CO2 emissions of six Japanese cities in 1980 and 2000 using the "four system boundaries" approach. The consumption-based emissions (i.e., system boundary No. 4) have not changed markedly over the study period. However, emissions associated with the other system boundaries have increased from 1980 to 2000. The consumption-based emissions should be adopted by local authorities in their pursuit of urban mitigation goals. Abstract: Cities can play a critical role in mitigating climate change. Although several carbon accounting methods have been proposed to identify mitigation responsibility of cities, there is still no single common and widely accepted method. In this study, we have adopted a method that is based on four system boundaries to identify and compare per capita CO2 emissions of six large Japanese cities in 1980 and 2000. Despite the fact that substantial differences exist among these cities in terms of industrial structure and transformation, population, and local climatic conditions, we found that the per capita CO2 emissions for the system boundary 4, which is CO2 emissions attribution to city from the consumption perspectives, are very similar among them and are stable over the 20-year study period, although those for all the other system boundaries are not similar. This is in contrast to the general claims made by local authorities regarding their success in reducing per capita CO2 emissions. Such claims are made on the basis of emissions estimated using the system boundary 2 method. We argue that using the system boundary 4 provides a more realistic account of changes in urban CO2 emissions and trends and should be adopted by local authorities in their pursuit of urban climate change mitigation goals.